Answer:
E. x^2 = 39 + 10x
Step-by-step explanation:
It helps to do one piece of the sentence at a time.
"A number, x, squared is 39 more than the product of 10 and x"
x
"A number, x, squared is 39 more than the product of 10 and x"
x^2 =
"A number, x, squared is 39 more than the product of 10 and x"
x^2 = 39 +
"A number, x, squared is 39 more than the product of 10 and x"
x^2 = 39 + 10x
Answer: E. x^2 = 39 + 10x
This is a system of equations.
First, you set everything in terms of y.
Take the first equation and move set everything equal to y
y=0+2x
Since it’s 0, you don’t need to put it, so
y=2x works.
Then, you plug y=2x into the bottom equation, for the y.
-7x +3(2x)=2. You do this because now you have the same variable for both and it can be solved easily.
Then you can simplify.
-7x+3x = 2
Then combine like terms.
-4x = 2
Divide by -4 on each side.
x = -1/2
So, now that you have x, you can plug in your x-value back into the top equation.
-2(-1/2) + y = 0
Combine like terms
1+y=0
Get y by itself
y=-1
There you have it!
You can check by plugging in both values to any of the equations. We will use the top one here.
-2(-1/2) + (-1) =0
+1 + -1 = 0
It works!
So,
X= -1/2
Y= -1
Please rate me Brainliest answer :)